Proposal of 100% renewable energy production for the City of Cuenca- Ecuador by 2050. (June 2021) - Icaza, Daniel; Borge-Diez, David; Galindo, Santiago Pulla
Abstract: This research presents a scenario for a 100% renewable energy system for the City of Cuenca, Ecuador, with a projection to the year 2050. The transition process starts with Ecuador's change in the productive matrix with reforms from the legal and business strategies point of view to the year 2050. Advances in energy material are dependent on political uncertainty both at the country (Ecuador) and local (Cuenca) levels. It is possible to stop using fossil fuels due to the implementation of new renewable energy sources, potentially rich in the Ecuadorian Southwest and evidenced in the National Plan for a Lifetime. Currently, there is evidence of accelerated changes concerning legal regulations, including the construction of several electric power generation plants. This change in the national productive matrix implies, among others, the implementation of electric vehicles and the change of natural gas stoves for electric ones, and the implementation of the "4 Rios" tram that crosses the city from North-South and South-North, incorporating 100% renewable energy generation, which would provide heat in urban and marginal urban areas. All the systems created in Ecuador, such as heating, cooling, transportation, security etc., will allow an increasing penetration of renewable energy until it reaches 100%. Graphical abstract: Image 1 Highlights: The scenario is 100% renewable energy by 2050 in the City of Cuenca in Ecuador. The surrounding of the city of Cuenca have great renewable energy potential. A more environmentally friendly approach is proposed. Reference horizon achievable by 2050 based on its energy wealth. Harmonious development of the city of Cuenca inserted in the Ecuadorian context.